What are the symptoms : exploring depression, anxiety and concussion symptoms among Icelandic male athletes - Karl Elí Karlsson 1993- (2022)
The aim of the current study was to examine the frequency and severity of concussion-, depressive-, and anxiety symptoms based on concussion history, as well as to examine the association between those symptoms. Participants in the current study were 366 Icelandic male athletes, ages 18-45 (M = 27.84, SD = 7.14), who played and/or trained at an elite level in football, basketball, handball, ice-hockey or combat sports in Iceland. Participants answered an online questionnaire that asked about their background and concussion history, as well as SCAT5 scale measuring concussion symptoms, the PHQ-9 scale measuring depression symptoms, and GAD-7 measuring anxiety symptoms. There were significant differences among groups of participants with different concussion histories in 12 out of 22 items on the SCAT5. Likewise, there were significant differences among groups of participants with different concussion histories in six out of nine items on PHQ-9, and for three out of seven items on GAD-7. Furthermore, all items on SCAT5 were significantly correlated with all items on PHQ-9, and all but two items were significantly correlated between SCAT5 and GAD-7. Participants with a history of concussion(s) scored higher on some items on the SCAT5, PHQ-9 and GAD-7. The items on the SCAT5 are associated with items on both the PHQ-9 and GAD-7, but the correlation is not strong. Results indicate that those who had sustained multiple concussions experienced more severe symptoms. Results also indicate a significant correlation between all items on SCAT5 and PHQ-9, but the correlation is weak overall. Keywords: Concussion, athletes, depression, anxiety, overlap of symptoms